Polia imbrifera Cloudy Arches - Pogue, Michael G. (Zenodo, 2010)
20. Polia imbrifera (Guenée) Cloudy Arches (Fig. 38, Map 21) Identification: Forewing length 21–26 mm. Frons has a black horizontal stripe below antennae. The male antenna is serrate and is filiform in the female. This is a large dark gray species with prominent white orbicular and reniform spots that are suffused with gray and bordered by black scales. Claviform spot is gray with a black border. Proximal to the subterminal line are various sized black triangulate spots with the largest an oblong spot just above the tornus. Hindwing is dark gray with a faint postmedial line. Flight period: June to early August and one record from mid-October, apparently double brooded in the Park. MAP 21. Collecting localities of Polia imbrifera. Collected localities: North Carolina: Haywood Co., Balsam Mtn. picnic area on Flat Creek trail, Flat Creek trail on Balsam Mtn. road, Mt. Sterling Trail, Hemphill Bald trail at Polls Gap on Balsam Mtn. road, Purchase Knob, 1 mi SE of Purchase house off Purchase Road in forest, Purchase Knob 1.1 rd. mi from house, Purchase Knob at house, Purchase Knob Ferguson cabin, Purchase Knob E of house in field, Purchase Knob NW of house in forest, Purchase Knob on road in meadow, Rough Fork trail at Polls Gap on Balsam Mtn. road 6.1 mi N of Blue Ridge Parkway; Swain Co., Noland Divide trail 1.2 mi NE on Clingman’s Dome parking lot, 3.3 mi NE of Clingman’s Dome parking lot on Fork Ridge trail, Indian Gap on Clingman’s Dome road, 5.6 mi SW of Jct. 441 and Clingman’s Dome Rd. on Noland Divide trail, Upper Noland Divide Trail ca. Clingman’s Dome. Tennessee: Blount Co., 2.5 mi from Rt. 321 on Foothills Parkway West; Sevier Co., 1.3 mi W of Jct. 441 and Clingman’s Divide road on Road Prong trail. (82 specimens) Elevation range: This is typically a high elevation species ranging from 4630–6000 ft. (1411–1829 m), but there is one record from 1600 ft. (411 m) along the Foothills Parkway. General distribution: Distributed across Canada from Newfoundland and Nova Scotia to British Columbia. In the U.S. this ...